Double-faced diffusive gradient in thin films sampler (df-DGT): Proposing an improved DGT sampler design for water deployments - Menegário, Amauri Antonio [UNESP]; de Almeida, Eduardo; Zanatta, Melina B. T. [UNESP]; Moreira, Luiz F. P. P. [UNESP]; Zóia, Leonardo H. [UNESP]; Viana, José Lucas M. [UNESP]; Kiang, Chang Hung [UNESP] (Elsevier, 2025)
Background: The Diffusive Gradients in Thin Films (DGT) technique has become the most widely used passive sampling method for inorganic compounds. This widespread adoption can be partly attributed to the development of new binding phases that facilitate the sampling of numerous analytes. In contrast, to date, the DGT sampler for inorganic compounds has not seen any significant design improvements. In this manuscript, a new design for the DGT sampler is proposed. The new design, referred to as the Double-Faced DGT (df-DGT) sampler, features dual sampling windows, enabling a twofold increase in analyte mass uptake compared to the conventional DGT sampler. Results: The proposed sampler was characterized for Cd, Co, Mn, Ni, and Zn by performing the following tests: deployment curves, the effect of the diffusive boundary layer (DBL), pH, ionic strength and deployment in synthetic samplers. It was demonstrated that the df-DGT sampler can accumulate twice the mass over time compared to the conventional DGT sampler. The effects of the DBL, pH, and ionic strength on the measurements of Cd, Co, Mn, Ni, and Zn, when sampling with the df-DGT, were consistent with those previously reported for the conventional DGT sampler. When the df-DGT sampler and the DGT sampler were deployed simultaneously in synthetic samples with varying concentrations of Cd, Co, Mn, Ni, and Zn, no significant differences were observed (at the 95 % confidence level) in the results obtained from both samplers. Significance: To the best of our knowledge, this is the first time a new DGT sampler, featuring conceptual innovations, is being proposed for sampling inorganic species in water. The proposed sampler is twice as effective in terms of mass uptake and is useful for short deployments or enhancing sensitivity. In the future, the application of this sampler could potentially be expanded to other uses, such as o-DGT.